Milk Producers’ Awareness of Milk-Borne Zoonoses In Baghabarighat Milk Shed Areas of Bangladesh (Research in Agriculture Livestock and Fisheries, 2023)
The present study was undertaken to assess the farmers’ knowledge and awareness of milkborne zoonoses in Bhaghabarighat Milk Shed Areas of Bangladesh. A cross-sectional study was carried out in randomly selected 270 dairy farmers in Pabna and Sirajgonj district. A pretested structured questionnaire was used to collect information from respondents regarding different aspects of milk-borne zoonosis. Data were collected from farmers, with inclusion criteria of having at least 2 cows with farming experience of more than 6 months. The study showed that almost 80% of the farmers were unable to name any milk-borne zoonotic disease, whereas rest of the farmers had a little bit knowledge about milk-borne zoonoses those were relatively educated and experienced farmers. About 23% of the farmers had no knowledge of the fact that raw milk can be a potential source of disease transmission. The majority of the respondents (99%) did not receive any formal training about zoonotic diseases. Among the respondents’ awareness levels of milkborne zoonoses were 4.5%, 9.2%, 17.4%, 54.84% and 82.1% for brucellosis, anthrax, tuberculosis, mastitis and diarrhea, respectively. The behavioral practices of dairy farmers observed to increase the risk of milk-borne zoonoses transmission were: consumption of raw milk (13%), lack of cooling system (100%), no milk routine testing, and none farmers’ did medical check-up. 87% of the respondents preferred to use boiled milk. The farmers’ overall knowledge about milk-borne zoonoses was inadequate. In conclusion, awareness and training programs about milking hygiene and handling can improve disease control and reduce the public health risk of milk-borne zoonoses.Vol. 9, No. 3, December 2022: 307-312